Fish Trading Transactions at Fadel Dela Buli Market, Maba District : A Review from the Perspective of Islamic Economic Law - W.D Aisa Desintia; Nirwan Umasugi; Jasmin Jasmin; Basaria Nainggolan; Zainal Abidin Marasabessy (Al-Hiwalah: Journal of Sharia Economic Law, 2026)
This study examines fish trading practices at Fadel Dela Buli Market, Maba District, from the perspective of Islamic Economic Law. The research focuses on transparency issues, price-quality discrepancies, and fairness in transactions. A qualitative field research approach was applied through observation, interviews, and documentation. The findings reveal that several trading practices do not fully comply with sharia principles, particularly in terms of honesty (shidq), fairness (‘adl), and avoidance of uncertainty (gharar). Non-transparent information regarding fish quality and inconsistent pricing mechanisms often disadvantage buyers. From the perspective of Islamic Economic Law, such practices are categorized as ethically problematic and potentially invalid due to elements of deception (tadlis). The study recommends strengthening ethical awareness among traders and improving market supervision to ensure fair and transparent transactions aligned with sharia principles